2021
DOI: 10.21138/bage.3153
|View full text |Cite
|
Sign up to set email alerts
|

Cartographies on COVID-19 and functional divisions of the territory: an analysis on the evolution of the pandemic based on Basic Health Areas (BHA) in Castile and Leon (Spain)

Abstract: In the face of the confusion and uncertainty that COVID-19 has caused over the last year, Geography has proven to be a useful aid in the interpretation of the spatial dynamics that explain the transmission of the virus. Applied cartography and GIS analysis of epidemiological data have been consolidated as essential tools for interpreting the health crisis. This paper explores the usefulness of maps for the study of the evolution of the pandemic in Castile and Leon, one of the Spanish regions with the highest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…One of the most relevant results of the study is the method to assess the hazard of contagion. The method is based on creating new spatial analysis units based on the movement of the infected people, which has been already proved to be effective in previous studies [18,24,40]. This approach contrasts other studies that assess the transmission of the virus and contagion hazard based on summing infected people at administrative units [10,11,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most relevant results of the study is the method to assess the hazard of contagion. The method is based on creating new spatial analysis units based on the movement of the infected people, which has been already proved to be effective in previous studies [18,24,40]. This approach contrasts other studies that assess the transmission of the virus and contagion hazard based on summing infected people at administrative units [10,11,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, De Cos et al [24] provided information about the COVID-19 spatial patterns at a neighborhood scale with a spatial-temporal perspective. López et al [40] showed the different impact of the virus between urban and rural areas, highlighting the errors introduced by the functional division of the territory, such as the health analysis units. Finally, Perles et al [18] addressed the errors that led to a wrong definition of the transmission pattern within a city and proposed as an alternative the use of accurate hazard maps, including spatial-temporal information of active focuses of contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Andrés López et al. ( 2021 ) analyze the COVID distribution in the region of Castilla y León (Spain) and show a lower impact of the disease in rural areas and a high concentration in urban centers. Fernández García et al.…”
Section: Introductionmentioning
confidence: 99%
“…The study identifies patterns of concentration of positive cases in buildings with neighborhoods with residential function and economic activities. Andrés López et al (2021) analyze the COVID distribution in the region of Castilla y León (Spain) and show a lower impact of the disease in rural areas and a high concentration in urban centers. Fernández García et al ( 2021) evaluate the temporal and territorial dimension of the pandemic in Asturias (Spain).…”
mentioning
confidence: 99%